(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In this paper, we ask why is there evil in the universe? The answer is that it is the very fact that there is a universe necessitates evil. It is the tension created between pure goodness and pure evil that leads to a universe of Energy=-1. We provide the calculations form Astrotheology to show that this is the case.